(untitled) - Plunian, Franck; Gomez, Paul; Alboussière, Thierry (Comptes Rendus. Physique, 2025)
Following the success of the experimental Fury dynamo [1], we are studying (i) the possibility of a new experiment with the same geometry and the same anisotropic electrical conductivity, but with a wider galinstan gap between the rotor and the stator than in Fury, in order to allow richer dynamics via Lorentz forces. Of course, to do this, we must first be able to start the dynamo with a large gap, which is the first objective of this study. The second objective (ii) is to design a miniature dynamo experiment, smaller than Fury, and with a narrow gap comparable to that of Fury. The use this time of anisotropic magnetic permeability instead of anisotropic electrical conductivity is the most appropriate solution. Theory shows that without a gap, using one rather than the other does not change the threshold of the dynamo, and only the direction of rotation of the rotor has to be reversed [2]. With a gap filled with galinstan, even a very narrow one, and unlike Fury whose rotor and stator were mainly made of copper, here the use of iron leads to a significant jump in magnetic permeability with galinstan, which could be detrimental to the dynamo. In order to study these two issues relating to (i) the thickness of the gap, and (ii) the electromagnetic properties of the material filling the gap compared with those of the rotor and stator, we need to solve the problem of the three-body anisotropic dynamo: the rotor, the gap and the stator.